(untitled) - Darst, David M. (New York, 2008)
Covers the historic market events, instruments, asset classes, and economic forces that investors need to be aware of as they create asset-building portfolios. This book explains how to use modern asset allocation concepts and tools to augment returns and control risks in a wide range of financial market environments.
Keywords: Asset allocation,Phân bổ tài sản